Konsumsi Makanan Ultra Proses sebagai Faktor Resiko Kejadian Obesitas pada Remaja - Masdalis Masdalis; Husnul Khatimah; Dinda Tri Lestari; Reski Pebriani (Journal of Telenursing (JOTING), 2026)
This study aims to examine the relationship between ultra-processed food consumption and obesity in adolescents. The study employed a quantitative method with a cross-sectional design. The results, based on statistical tests, showed a relationship between ultra-processed food consumption and obesity (p=0.03). In conclusion, there is a relationship between ultra-processed food consumption and obesity. High consumption of ultra-processed foods contributes to an increased risk of obesity in adolescents.   Keywords: Ultra-Processed Food, Obesity, Adolescents